Self Management dalam Meningkatkan Disiplin Belajar Siswa - Mashurin, Mashurin; Fadkhurosi, Adnan (Universitas Muria Kudus, 2023)
The purpose of this study is to investigate the efficacy of self-management strategies in enhancing student learning discipline.This study is experimental in nature.A non-equivalent control group design model and a quasi-experimental design were used in the design.The participants in this study were 138 seventh-grade students from SMP Negeri 2 Mlati Sleman.Purposive sampling was used to collect samples from the experimental group of five students.Utilizing a questionnaire, data are collected.The Mann Whitney test was used for the method of data analysis.The findings revealed:1) Student learning discipline was improved by self-management strategies (p = 0.005 0.05).The experimental group's learning discipline's pretest averaged 66.00, an increase of 144.60.The control group's average score on the pre-test, 68.40, and the post-test average, both increasing to 85.20; and (2) learning discipline is influenced by self-management by 97.2%.